Performance of aerodynamic baffles in cylindrical grinding analyzed on the basis of air layer pressure and speed - Catai, Rodrigo Eduardo; Da Silva, Leonardo Roberto; Bianchi, Eduardo Carlos [UNESP]; De Aguiar, Paulo Roberto; Zílio, Felipe M.; De Domenico Valarelli, Ivan; Salgado, Manoel Henrique (Springer Nature, 2008)
Over the years, grinding has been considered one of the most important manufacturing processes. Grinding is a high precision process, and the loss of a single workpiece in this stage of the production is unacceptable, for the value added to the material is very high due to many processes it has already undergone prior to grinding. This study aims to contribute toward the development of an experimental methodology whereby the pressure and speed of the air layer produced by the high rotation of the grinding wheel is evaluated with and without baffles, i.e., in an optimized grinding operation and in a traditional one. Tests were also carried out with steel samples to check the difference in grinding wheel wear with and without the use of baffles. Copyright © 2008 by ABCM.
Keywords: Aerodynamic baffle; Grinding; Optimized process